Avaliação de tratamentos endodônticos através de exame clínico, radiográfico e de tomografia computadorizada de feixe cônico em casos sintomáticos. - França, Roberta Moreira (2013)
This research that aimed to evaluate endodontic treatments performed by undergraduate dental UFPB and factors for failure by clinical examination, radiographic and symptomatic cases in CBCT. Were selected 120 patients through analysis of 557 medical records are on file in the Department of Endodontics that were seen between the years 2007 to 2011. The patients' ages ranged from 15 to 78 years, 31 were male and 89 were female. The diagnosis chronic apical periodontitis was 50% of cases, followed by chronic periapical abscess (15.0%). With respect to dental group the most frequent were upper central incisors (28.3%) and pre-molars (24.2%). As for the number of sessions required to treat 59.2% of the cases was conducted in three sessions. The time of follow up ranged from 1 ½ years to 4 ½ years. Regarding the clinical management 73.3% the patients had no signs or symptoms, but the rest of the sample signs and symptoms were: 11.7% pain only by percussion and 3.3% pain by percussion with mobility. The presence of blackened crown was recorded in 37.5% of cases. The majority of patients had appropriate endodontic treatment (72.5%), keeper intracanal absent (88.3%) and adequate coronal restoration (74.2%). Most radiographic images in the index PAI showed normal appearance bringing a success index (PAI 1 + PAI 2) 70%. In index Strindberg most (62.5%) of the treatments were considered successful, with 30.0% uncertain healing and 7.5% failure. The percentage with endodontic treatment and adequate coronal restoration and success in Strindberg and PAI index was highest among those who had no signs and symptoms, with a significant association. The percentage of cases with endodontic treatment and adequate coronal restoration was higher among cases successfully than among uncured, with significant association. The success rate by Strindberg and PAIwas higher among cases with vital pulp than pulp necrosis. A significant association between the index PAI and the index CTCTPAI, but the measures tomography and radiography, the mean and median were higher in CT than on radiographs, significant difference betweenthe two methods.Concludes that the clinical and radiographic examinations are important in the process of preservation endodontic, but the CBCT is more suitable for this type of diagnosis, due to higher sensitivity and specificity in evidence of endodontic failure.